CONCEPT AND IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN BUSINESS PERFORMERS - Sugiyanto Sugiyanto; Makhda Intan Sanusi (SEAN Institute, 2023)
Concept and Implementation of Islamic Business Ethics in Business Performers. This research aims to find out the concept and application of Islamic business ethics for business actors. The aim of this research is to find out the concept of Islamic business ethics and how it is implemented for business actors so that it is hoped that the results of this research can be used as a model for other business actors. The research carried out was descriptive using previous literature. The results showed that the business environment around Sendang village had implemented Islamic business ethics, both by entrepreneurs and their employees. In carrying out businesses and activities, business actors have understood and implemented Islamic principles or values based on the Qur'an and Hadith. The implementation of Islamic business ethics includes four aspects: principles, management, marketing/advertising and products/prices and also the implementation of Islamic business ethics is measured through five principles, namely the principles of monotheism, honesty, usefulness, responsibility and justice .